Midwife Professionalism and Patient Satisfaction in Reproductive Midwifery Services: A Quantitative Study - Herliana, Herliana (Jurnal MIDPRO, 2024)
Maternal and infant mortality rates in Indonesia remain a health issue that requires serious attention, especially in regions with limited healthcare facilities. Midwives' professionalism is essential in addressing this issue, as midwives are the primary providers of reproductive midwifery services. This study aims to identify the relationship between midwives' professionalism and patient satisfaction at PMB Nurhasanah, Bandar Lampung. The study employs a descriptive correlational design with a quantitative approach, involving 114 respondents selected using purposive sampling. The research instrument is a questionnaire that assesses midwives' professionalism through aspects of competence, ethics, communication, and empathy and measures patient satisfaction levels. The results show that most respondents (51%) rated midwives' professionalism as high, while 78% expressed their satisfaction at a moderate level. Pearson correlation analysis indicates a significant relationship between midwives' professionalism and patient satisfaction (p-value = 0.017), suggesting that improving midwives' professionalism positively correlates with increased patient satisfaction. These findings align with previous research, highlighting that midwives' professionalism, especially in communication and responsiveness, dramatically affects the quality of maternal and child healthcare services. Based on these results, this study recommends continuous training focused on developing ethics and communication skills for midwives. Furthermore, this study contributes to a deeper understanding of patient satisfaction factors. It encourages policies to strengthen midwives' professionalism to improve the quality of midwifery services locally.